2022
DOI: 10.1155/2022/1131235
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lactate Dehydrogenase Is a Sensitive Predictor of Systemic Complications of Acute Pancreatitis

Abstract: Background. Acute pancreatitis (AP) is a common and potentially life-threatening inflammatory disease that can cause various complications, including systemic inflammatory response syndrome (SIRS), pleural effusion, ascitic fluid, myocardial infarction, and acute kidney injury (AKI). However, there is still a lack of rapid and effective indicators to assess the disease. The aim of this study was to investigate the associations of high serum lactate dehydrogenase (LDH) levels with AP severity and systemic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…Similar to previously published studies, in our research, LDH was correlated with organ failure, since it was suggested that pancreas dysfunction was not the initial cause for the raised LDH levels, but the kidney dysfunction should be considered [19].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previously published studies, in our research, LDH was correlated with organ failure, since it was suggested that pancreas dysfunction was not the initial cause for the raised LDH levels, but the kidney dysfunction should be considered [19].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, PE was detected by chest X-ray in eight studies [ 16 , 18 , 20 , 22–24 , 41 , 50 ], by CT in 14 studies [ 19 , 21 , 25–27 , 30 , 32 , 35 , 38 , 39 , 42 , 45–47 ], by transthoracic sonography in one study [ 17 ] and by combination of above methods in four studies [ 29 , 31 , 48 , 49 ]. Other studies did not clearly report the detecting method [ 28 , 33 , 34 , 36 , 37 , 40 , 43 , 44 ]. The general characteristics of the eligible studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Creatinine máu tăng cao trong vòng 48 giờ đầu tiên có thể dự đoán sự phát triển của hoại tử tuyến tụy. Tian thấy rằng mức độ LDH ở bệnh nhân AP nặng cao hơn khoảng hai lần so với bệnh nhân AP nhẹ và tác giả báo cáo rằng LDH là yếu tố dự đoán đáng tin cậy của AP nặng (độ nhạy 82,7% và độ đặc hiệu 96%) [9]. Ngoài ra, một mô hình sử dụng LDH để dự đoán AP nặng, cho thấy 63,6% bệnh nhân được xác định là mắc AP nặng tại LDH> 536 U/L và độ chính xác tổng thể của mô hình là 88,5%.…”
Section: Bàn Luậnunclassified